Características fisicoquímicas y determinación del porcentaje relativo de sus componentes hidrocarbonados y oxigenados de la raiz de cúrcuma longa l. (cúrcuma) procedente de la selva peruana – Madre de Dios - Aguirre Acevedo, Yvan Willian (2016)
In this research, essential oil root longa L. Turmeric (Curcuma) was obtained using the distillation technique by steam water in order to be able to subsequently analyze their percentage yield, their physicochemical characteristics (color, odor, flavor and texture), also physical parameters such as relative density, refractive index, solubility in different solvents as water, alcohol 50 °, 70 °, 80 ° and 96 °, n-hexane and ethyl ether was analyzed. Finally chemical parameters were also evaluated as the acid, which is important in the control of an essential oil